From stress to screen: family factors on the path to problematic media use in children aged 4–11 - Yayla, İbrahim Erdoğan; Makas, Samet; Yıldırım, Selami; Dombak, Kübra; Çelik, Eyüp (Frontiers in Psychology, 2025)
ObjectiveToday, the rapid development of digital technologies fundamentally transforms how children interact with media. This research examines the mediating roles of parenting stress and problematic media use in children on the relationship between digital parenting awareness and family harmony.MethodsThe data for this study were obtained from 502 parents with children aged 4–11 years. Participants’ daily screen time was 1–2 h (55.8%), 2–3 h (26.9%), 3–4 h (12%), 4+ h (5.4%). Convenience sampling was the method employed for the present study. Correlation analysis and structural equation modeling were performed to analyze the data.ResultsThe correlation analysis concluded that all variables were interrelated. Furthermore, the structural equation model demonstrated that parenting stress and problematic media use mediated the relationship between digital parenting awareness and family harmony.ConclusionThis study has contributed to understanding the relationship between parenting stress and problematic media use in childhood, as well as the variables that mediate this relationship. It has provided a new perspective on the variables that should be focused on in preventing and intervening in children’s problematic media use behaviors. Practically, the research results provide a valuable reference for university educators, assist school counselors in reducing students’ problematic media use behaviors through education, and help parents improve their skills in raising their digital awareness.